Respuesta :

Answer:

[tex](x-\frac{1}{2})^2=\frac{81}{4}[/tex]

Step-by-step explanation:

Hi there!

[tex]x^2-x-20=0[/tex]

This equation is written in the form [tex]ax^2+bx+c=0[/tex]. First, use partial factoring:

[tex](x^2-x)-20=0[/tex]

For x^2-x, the b value is -1 in [tex]ax^2+bx+c[/tex]. To complete the square, take the square of half of 1 and add it in the parentheses as the c value:

[tex](x^2-x+\frac{1}{2}^2 )-20=0[/tex]

However, when adding values to one side of the equation, we must to the same to the other side:

[tex](x^2-x+\frac{1}{2}^2 )-20=\frac{1}{2}^2[/tex]

Complete the square:

[tex](x-\frac{1}{2})^2-20=\frac{1}{4}[/tex]

Move 20 to the other side

[tex](x-\frac{1}{4})^2=\frac{1}{4}+20\\(x-\frac{1}{2})^2=\frac{81}{4}[/tex]

I hope this helps!